Psycho-emotional profile and professional competence of trainees pre-cycle "neurology" in circumstances of the postgraduate education system restructuring - Паєнок, Анжеліка Володимирівна; Січкоріз, Орест Євгенович (ScienceRise: Medical Science, 2016)
In order to investigate psycho-emotional profile of neurologists, studying on pre-cycle "Neurology", in circumstances of constant reforms of both medical field, and postgraduate education, their test in writing (51 person) was carried out by standardized multifactor personality test. The given method allowed determining quantitatively and qualitatively (in points) existing psycho-emotional problems of this category of neurologists independently of age, sex and work experience, e.g.: the presence of emotional lability with psycho-astenisation and autisation, as well as reserve mechanisms of adaptation increasing (communicability and expansion of social desirability). Materials and methods. The additional test of the level of special professional skills in the given group at the beginning and in the end of studying on the 30-day pre-cycle showed a probable improvement of the knowledge level, according to the complex theses data, therefore, it can be argued about the presence of motivational factors in students to expand and to improve their knowledge in specialty during postgraduate training. Results of the conducted research of neurologists’ psycho-emotional profile have shown the presence of emotional lability with psycho-astenisation and autisation under constant reforms of medical field conditions. Nevertheless, in contrast to the specified profile changes, the adaptive desire of both special knowledge expanding, and active participation in the mentioned changes are formed in modern students. Conclusion. In order to reduce psychological disadaptation problems manifestation in modern pre-curses students, it should more widely publicize and discuss the advisability of medical field reforms, both in available informational sources for doctors (social and medical publications, journals, associations and specialty societies meetings), and during studying at postgraduate education department. Understanding and appropriate positive perception of the necessity of changes in medical field will reduce effectively anxiety and pessimism among doctors